Fourier-transform Infrared Analysis and In Vitro Antibacterial Activity of Ormocarpum cochinchinense (Elumbotti): Fourier-transform Infrared Analysis and In Vitro Antibacterial Activity of Ormocarpum cochinchinense (Elumbotti) - Thirumal, Sivakumar (International Journal of Pharmaceutical & Biological Archive, 2019)
The present research is to assess the Fourier transform infrared (FT-IR) analysis and antibacterial activities of Ormocarpum cochinchinense leaf extract using different solvents dimethyl sulfoxide (DMSO), ethyl acetate, ethanol (EtOH), methanol (MeOH), and chloroform. To investigation of FT-IR analysis and antibacterial activities become used agar well diffusion method. FT-IR vibrational bands confirmed that the fractions of O. cochinchinense had lots of biologically active compounds which include H–Bonded Phenols, alkanes, carboxylic acid, carboxylic acid, flavonoids, polyphenols, catechins, aromatics, and aliphatic amines. Antibacterial activity showed that the strongest activities had been produced by MeOH solvent reaction with all the human pathogens. This research may be concluded that MeOH solvent extract of O. cochinchinense might be a capability for the treatment of antibacterial activities.